Information disclosure and financial performance among Malaysian public listed companies / Nurazrin Mat Tarmezi - Mat Tarmezi, Nurazrin (2015)
Corporate scandals in Enron, WorldCom and Countrywide Financial have raised global attention towards the need for companies to be transparent. Managers’ misbehavior and false evaluation are resulted from the information asymmetry that exists between managers and other stakeholders. KPMG had conducted a survey on fraud, bribery and corruption in Malaysia and found that one of the factors is due to insufficient disclosure, which provided rooms for managers to act illegally. Towards promoting transparency among companies in Malaysia, Bursa Malaysia has introduced CD Guide in 2012 to guide companies in providing high quality and standard information. Objective of this study are to investigate the level of information disclosure among Malaysian public listed companies, to examine whether CD Guide does make changes in the level of information disclosed and also to examine the relationship between the level of information disclosure and companies’ financial performance. This study is motivated by the inconclusive results from previous studies. Companies’ performance are indirectly affected by the need for greater information disclosure. As companies grow, they require huge funds. By disclosing greater information, it enables investors, bankers and other financial institutions to understand the activities, operations and performance of the companies, as well as evaluating the management’s accountability towards financial reporting before approving any fundings. A total of 106 listed companies in Bursa Malaysia have been selected, 318 annuals reports have been reviewed and all data have been analyzed by using SPSS version 21. Information disclosure indices are extracted from the annual reports whereas the financial performance’s components are extracted from Datastream or Thomson Reuters. The results reported that majority of the public listed companies in Malaysia have a high level of information disclosure score and are providing continuous efforts to disclose more after the introduction of the CD Guide by Bursa Malaysia. On top of that, the level of information disclosure is found to have a positive relationship towards companies’ financial performance in terms of their ability in creating value for shareholders on the equity invested and ability to compete in the financial market. However, no relationship is found on the ability to increase earnings and efficiency in managing assets. This study not only provides feedback to Bursa Malaysia on the effectiveness of the CD Guide introduction, but also creates awareness among companies towards the need for greater information disclosure.